Implementation of Collaborative, Planning, Forecasting and Replenishment (CPFR) to Reduce the Bullwhip Effect in MSME Sate Madura Cak Kholil - Hamidi Sjurahudin; Resista Vikaliana (Yayasan Ilomata, 2022)
The aims of this study are: (1) to identify and analyze the estimated demand for chicken and goat satay products in the MSME of Sate Madura Cak Kholil; and (2) to find out the stock safety to overcome the surge in product demand at the MSME of Sate Madura Cak Kholil. The research method used is a descriptive method with a quantitative approach. The sample was determined based on a non-probability sampling technique using the purposive sampling method. The data used in this study included primary data and secondary data, namely data on supply and demand for the MSME of Sate Madura Cak Kholil. The results of the study indicate that the application of collaborative planning, forecasting, and replenish menthasan effect on reducing the bullwhip effect in the MSME of Sate Madura Cak Kholil.